Rural health frontiers: exploring insights, lessons, and priority actions identified through a global 40-speaker webinar series on rural health equity - Theadora Koller; Alan Chater (James Cook University, 2023)
Introduction: Tackling rural health inequities requires equity-oriented approaches within health systems (eg across human resources, service delivery, information systems, health products, governance, financing) and action at cross-sectoral levels and with communities to address social and environmental determinants.Methods: During the July 2021 to March 2022 period, more than 40 experts contributed to an 8-part webinar series on rural health equity, sharing experiences, insights and lessons learnt for both systems strengthening and action on determinants. The webinar series was convened by WHO in collaboration with WONCA’s Rural Working Party, OECD and agencies in the UN Inequalities Task Team subgroup on rural inequalities.Results: From rural proofing to advancing a One Health approach, to research on barriers to health services, to ensuring an Indigenous health focus and community engagement in medical education, the series covered a range of topics relevant to diminishing rural health inequities.Discussion: The 10-minute presentation will highlight emerging lessons, where more research activity, deliberation in policy and programming domains, and joined up action across stakeholders and sectors have been called for.